PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL, DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Putra Widyatmika, I Dewa Gede Agung; Riana, I Gede (E-Jurnal Manajemen; Vol 9 No 10 (2020)DO - 10.24843/EJMUNUD.2020.v09.i10.p04, 2020)
The aim of the research is: to know the influence of transformational leadership on the work center and organisational commitment at Hotel Pita Maha Resort & Spa Ubud, to find out the impact of work satisfaction on organizational commitments at Hotel Pita Maha Resort & Spa Ubud, and to find out the role of job satisfaction mediation on the influence of transformational leadership on organizational commitment to Hotel Pita Maha The population used in this study was all employees working at the Hotel Pita Maha Resort & Spa Ubud which amounted to 102 people. The number of employees of Hotel Pita Maha Resort & Spa Ubud in 2018. The samples were determined by 102 people with saturated sampling techniques. Data collection is done by spreading the questionnaire directly to the employees of Hotel Pita Maha Resort & Spa Ubud and analyzed using the average descriptive statistical count as well as classic assumption test and line analysis and Sobel test. Data analysis results show that a variable of transformational leadership is positive and significant towards job satisfaction, job satisfaction variables have a positive and significant effect on organizational commitments, variable transformational leadership is positively and significantly impacting the organizational commitments and job satisfaction variables have been positive and significant in the partial process of the influence of transformational leadership towards the organizational commitments at Hotel Pita Maha Resort & SPA Ubud. Keywords: organizational commitment, job satisfaction, transformational leadership